Das Haus neben den Gleisen - Gaul, Simone Catherina; Fingscheidt, Nora (Germany : Aug&Ohr Medien, 2016)
The women's shelter in Stuttgart has 50 rooms, 50 residents, and 50 destinies, and in the background we can recall the rattle of trains. Sylvia wants to get out of the shelter and back to her own apartment. Carola loves the place like her home, especially the view from her window. Gabi has come to terms with the situation and has started to make art in her new home. All of the women have one thing in common, they were without a roof over their heads and ended up in the Stuttgart women's shelter.
Verzio Film Festival Submission
Keywords: Documentary films